ANTIBIOTIC RESISTANCE AND PATHOGEN SHIFTS IN VAGINAL MICROBIOTA: A RETROSPECTIVE STUDY ON IMPLICATIONS FOR SUTURE SOAKING IN SURGICAL SITE INFECTION PREVENTION - Asal I. Buribaeva; Zulfiya I. Ixlosova (Central Asian Journal of Medicine, 2025)
Surgical site infections (SSIs) remain a critical challenge in gynecological surgeries, including those for genital prolapse. The vaginal microbiota, comprising diverse bacterial and fungal species, plays a pivotal role in SSIs by introducing pathogens into surgical sites. Understanding local bacterial flora and antibiotic resistance patterns is essential for developing targeted strategies, such as soaking sutures in antibiotics preoperatively. This study analyzes hospital data from 2019 to 2023 to identify prevalent vaginal pathogens and their antibiotic sensitivity, informing evidence-based suture-soaking protocols.